Avaliação linear do côndilo mandibular em indivíduos padrão face longa classe III submetidos a cirurgia ortognática - Anjos, Alexandre Ladeira Veloso dos (2017)
Facial esthetics is a current concern. The facial morphology was developed from the moment that there was an increase in the discordance in the plans of treatments for the same patient. Thus, it was possible to correct skeletal changes of the face, through orthognathic surgery, seeking a balance and facial harmony. The surgical procedure, with its side effects, such as recurrence, led to research on the correct positioning of the condyle, using cone-beam computerized tomography and state-of-the-art software, where it can be handled, measured and analyzed linearly. Regions of interest, obtaining greater predictability. The objective of this study was to evaluate the linear analysis of the right and left mandibular condyles in the sagittal plane after orthognathic surgery in standard long face class III patients using cone-beam computed tomography (CBTB) With the use of INVESALIUS 3.0® software (CTI - Renato Archer Information Technology Center, Campinas Brazil). The sample was composed of medical records of 13 individuals (08 women and 5 men), aged 18-60 years, with standard skeletal alteration Long Face, class III, all submitted to surgical procedures with defined protocol, being performed by the same Hugo Nary Clinic - Bauru, São Paulo Clinic. Results: There were statistically significant results for the linear analyzes of the right and left condyles. Conclusion: Linear analysis was not able to confirm if there was remodeling, condylar resorption, alteration of positioning by surgery or condylar torque